The Persistence and Market Valuation of Recurring Nonrecurring Items - Cready, William; Lopez, Thomas J.; Sisneros, Craig A. (The Accounting Review, 2010)
ABSTRACT: This study focuses on the persistence and market value implications of a subset of nonrecurring charges that are atypical due to repeated occurrence. The increased recurrence of supposedly nonrecurring items perhaps reflects managerial shifting of (more permanent) ordinary expenses to a transitory category or, alternatively, may reflect an environment where these items naturally occur more frequently. Either scenario suggests that these repetitive charges have future earnings implications dramatically different from truly nonrecurring events and should therefore be valued more like a recurring component of earnings. Consistent with this notion, we find that as the frequency of reporting negative special items increases (measured by the presence of multiple prior charges), the persistence of these items significantly increases with respect to future earnings. Our evidence also suggests that the valuation multiple on such charges increases with frequency. That is, the market values “recurring nonrecurring” items more like the other components of recurring earnings.